Transformation of Digital Payment: Determinants of Customer E-Money Adoption and Implications for Digital Intention Behavior - Satria Abadi; Merry Susanti; Miswan Gumanti; Kusnadi Kusnadi; Agnes Susana Merry Purwati (Moneter: Jurnal Keuangan dan Perbankan, 2026)
The rapid expansion of e‑money digital payments in Indonesia amid ongoing digital transformation raises questions about which factors drive adoption and shape users’ intentions to use digital payments. This study investigates the principal determinants of e‑money adoption and their influence on behavioral intentions among Generation Z. A random sample of Gen Z customers from several areas in Lampung Province completed a structured questionnaire. Data were analyzed using multiple linear regression to examine relationships among social influences, facilitating conditions, and attitude toward e‑money on digital payment behavior. The findings reveal that social influence, facilitating conditions, and attitude toward e‑money each have significant positive effects on e‑money usage behavior among Gen Z in Lampung. Further analysis shows that attitudes toward e‑money are significantly shaped by facilitating conditions and social influences. This study suggest that strengthening supportive infrastructure and leveraging social networks can enhance favorable attitudes and increase e‑money adoption among young consumers.In practical terms, this means fintech providers and policymakers should prioritize reliable transaction systems, better digital literacy support, and wider acceptance networks to encourage sustained use.repository.radenintan.